Telaah Sosio-Antropologis Praktik Tarekat âAlawÃ®yah di Gresik - Mahzumi, Fikri (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2014)
The following article gives reviews on roles of the Sufi path, Ê¿AlawÃ®yah Tariqa among âAlawÃ®yyÃ®n, to success their diaspora in Gresik regency using the socio-anthropological approach. It observes the âAlawÃ®yyÃ®n scholars as a group of migrants who adapt their Sufi path creatively with their new environment. Therefore, they have significant roles to keep their identity as âAlawÃ®yyÃ®n diaspora. It is found that rituals practiced by âAlawÃ®yyÃ®n in Gresik are reading rÃ¢tib, hawl and rawhah. In this context, the ritual has found aspects of theÂ socio-anthropological values, as it involves a series of human creativity that has been shaping the culture, communication, and mobility in the social environment. From our view, the practice of the Sufi path, âAlawÃ®yah Tariqa in Gresik, has become moral values that were internalized by its followers, and have been implemented by them as a behavior in the community. These rituals can keep their social-religious authority as ahl al-bayt (the descendants of Prophet Muhammad).